Business potential of arctic berry wax : Natural cosmetics industry - Helin, Mika (2021)
This thesis was a case study researching business potential for arctic berry wax as raw material in Norwegian natural cosmetics industry. The goal of the research was to compile a list of potential customers for arctic berry wax and to find out if demand for such product exists in the target market. Arctic berry wax is a wax substance that can be extracted from the side streams and waste of the berry industry. By using more already existing materials such as the waste accumulated from food processing and refining, the commercial utilization rate of berries as raw material increases. The thesis discusses the theory behind market research through marketing intelligence and customer acquisition. In the study of the phenomenon gets acquainted with both Nordic and global berry market from foraging the raw material to the high-quality berry end products. Quantitative research method was chosen to quantify the problem through generating numerical data which can be transformed into usable statistics. Attitudes, opinions and defined variables can be quantified. Quantitative research measures data to formulate facts and uncover patterns and trends in the research. For possible future studies about business potential of arctic berry wax it is recommended to create tangible marketing material for the prospects. Compiling a compact informative package on what arctic berry wax is and what it can be used will surely generate more appeal than handful of ideas and pages of academic writing. Service and product design for target customer segments could be used to help with creation of such marketing material.